Ganglioside GM1 interacts with the serotonin1A receptor via the sphingolipid binding domain - Prasanna, X.; Jafurulla, M.; Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica et Biophysica Acta, 2016)
Glycosphingolipids are minor yet essential components of eukaryotic cell membranes and are involved in a variety of cellular processes. Although glycosphingolipids such as GM1 have been previously reported to influence the function of G protein-coupled receptors (GPCRs), the molecular mechanism remains elusive. In this paper, we have explored the interaction of GM1 with the serotonin1A receptor, an important neurotransmitter receptor that belongs to the GPCR family. To examine the molecular basis of the interaction of GM1 with the serotonin1A receptor, we performed a series of coarse-grain molecular dynamics simulations of the receptor embedded in membrane bilayers containing GM1. Our results show that GM1 interacts with the serotonin1A receptor predominantly at the extracellular loop 1 and specifically at the sphingolipid binding domain (SBD). The SBD motif consists of a characteristic combination of aromatic, basic and turn-inducing residues, and is evolutionarily conserved in case of the serotonin1A receptor. The interaction of the SBD site with GM1 appears to stabilize a 'flip-out' conformation in which W102 of the extracellular loop 1 flips out from the central lumen of the receptor toward the membrane. The population of the 'flip-out' conformation is increased in the presence of cholesterol. Our data strongly suggest that a direct interaction between GM1 and the SBD site of the serotonin1A receptor may occur in vivo. In view of the reported role of GM1 and the serotonin1A receptor in neurodegenerative diseases, GM1-receptor interaction assumes significance in the context of malfunctioning of neuronal GPCRs under such conditions.